Bibliometric analysis of Journal of Natural Science, Biology and Medicine (JNSBM): The Editors perspective - Ahmed, K.K. Mueen; Kumar, Arun HS (Biology, Engineering, Medicine and Science Reports)
Bibliometric analysis is valuable matrix to understand the progress of any journal and is often essential to scope the journals publication strategy. Hence, we performed a Bibliometric evaluation of the Journal of Natural Science, Biology and Medicine (JNSBM) over past 7 years. Data from Scopus, SCImago, Google Scholar, in-house database and other indexing sites were collated and analysed. The key performance indicators were also identified, which are presented here.
Keywords: Bibliometrics; JNSBM; Analysis; Journal Impact; Journal performance; Indexing